2021
DOI: 10.1001/jamaophthalmol.2021.3331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Morphologic Characteristics of Fibroblast Growth Factor Receptor Inhibitor–Associated Retinopathy

Abstract: IMPORTANCE Fibroblast growth factor receptor (FGFR) 1 to 4 inhibitors are approved by the US Food and Drug Administration and suppress the mitogen-activated protein kinase (MAPK) pathway, with a potential for treatment-related retinopathy. To date, implications of FGFR inhibitor-associated ocular toxic effects are poorly described. Therefore, more detailed clinical descriptions of this ocular toxic effect could help explain visual symptoms while receiving drug therapy.OBJECTIVE To describe the clinical and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 9 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…SRD is also reported in patients treated with targeted therapies, such as MEK inhibitors, which modulate the MAPK pathway, causing eye disorders such as retinal detachment (at frequencies ranging from 5% to 38%) ( 15 ). Similar to MEK inhibitor-associated retinopathy, pemigatinib-induced retinopathy showed no substratum changes, including a distinguishable RPE, interdigitation zone (IZ), and ellipsoid zone (EZ) after fluid disappearance, unlike central serous chorioretinopathy, which is usually accompanied by hyperreflective foci, loss of hyperreflective IZ and EZ, and disturbed RPE after resolution ( 20 ). These tyrosine kinase inhibitor-related ocular toxicities are easily manageable in the clinical setting as they are immediately identified by patients and straightforward to confirm by prompt ophthalmic examination at the time of the first visual disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…SRD is also reported in patients treated with targeted therapies, such as MEK inhibitors, which modulate the MAPK pathway, causing eye disorders such as retinal detachment (at frequencies ranging from 5% to 38%) ( 15 ). Similar to MEK inhibitor-associated retinopathy, pemigatinib-induced retinopathy showed no substratum changes, including a distinguishable RPE, interdigitation zone (IZ), and ellipsoid zone (EZ) after fluid disappearance, unlike central serous chorioretinopathy, which is usually accompanied by hyperreflective foci, loss of hyperreflective IZ and EZ, and disturbed RPE after resolution ( 20 ). These tyrosine kinase inhibitor-related ocular toxicities are easily manageable in the clinical setting as they are immediately identified by patients and straightforward to confirm by prompt ophthalmic examination at the time of the first visual disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…7 A similar retinopathy has been more recently described among inhibitors of the upstream target, FGFR. 8,9 The majority of previous reports largely involved patients who had routine asymptomatic screening after initiation of treatment; in most cases the treatment is continued despite the presence of mild retinal dysfunction, which often resolves over time. 8,10 In our case, the patient became profoundly symptomatic with large areas of subfoveal fluid bilaterally as well as multifocal pockets of SRF.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The majority of previous reports largely involved patients who had routine asymptomatic screening after initiation of treatment; in most cases the treatment is continued despite the presence of mild retinal dysfunction, which often resolves over time. 8,10 In our case, the patient became profoundly symptomatic with large areas of subfoveal fluid bilaterally as well as multifocal pockets of SRF. Alekseev et al 11 reported a patient who developed similar OCT findings after treatment of pemigatinib, another small molecule inhibitor of FGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Additional demographics and patient-specific data were extracted retrospectively under an IRB approved protocol. One-hundred twentyeight eyes exhibited subretinal fluid on optical coherence tomography (OCT; previously published [7][8][9]) and were compared in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…In an effort to better understand this topic, this study systematically compared drug-induced retinopathy observed in patients undergoing FGFR, MEK, or ERK inhibitor treatment within prospective clinical trials. Data were pooled from previously published series on FGFR, MEK, or ERK inhibitor retinopathy [7][8][9] to explore differences among drug types with the intent of bringing ophthalmologists and oncologists a step forward to better balance benefits and harms of these drugs. In the present study, clinical and morphological characteristics were compared across patients receiving FGFFR, MEK, or ERK inhibition, along with the associated retinal, RPE, and choroidal changes of the fluid foci that were then compared with the drug-induced retinopathy.…”
Section: Introductionmentioning
confidence: 99%